Remote diffusion-weighted imaging lesions and blood pressure variability in primary intracerebral hemorrhage - Xu, Xuhua; Peng, Shuangshuang; Zhou, Yanli; Li, Jiawen; Tong, Lusha; Gao, Feng (Frontiers in Neurology, 2022)
Objective: The aim of this study was to examine the association between remote diffusion-weighted imaging lesions (R-DWILs) and blood pressure variability (BPV) in patients with primary intracerebral hemorrhage (ICH). Methods: We conducted a retrospective review of a consecutive cohort of 375 patients with primary ICH within 24 hours onset. R-DWILs were defined as hyperintensity lesions in DWI remote from the hematoma. Blood pressure recordings were extracted up to 24 hours postadmission. BPV was measured using standard deviation (SD), coefficient of variation (CV), and successive variation (SV). Results: Remote DWI lesions were detected in 65 (17.3%) primary ICH patients. In multivariable logistic regression analysis, parameters of BPV were independently associated with R-DWILs, and the results remained consistent after adjusted with mean SBP. SD, CV and SV values in the highest quintile, showed 3- to 8-fold increased risk of R-DWILs, compared with the lowest quintile. ΔSBP demonstrated significant difference in2 different predictive models. Max SBP only dictated significant difference in model 1. Mean SBP, admission SBP and min SBP, failed to present association with R-DWILs in model 1 or model 2. Conclusions: Our results provided additional evidence that BPV is associated with the development of R-DWILs in primary ICH.